ICT Teacher Capacity Building in Education: Lesson Learned From Successful Education Countries And Considerations For Transferring Into Indonesia Context - Sylvia Sylvia; Harmiati Harmiati (Edumaspul: Jurnal Pendidikan, 2024)
ICT teacher capacity building is one of SDG4's goals, and it is one of the 21st skills to face Education in 2030 and the 21st century. Even though ICT teacher capacity building has been introduced widely by many international organizations, reviewing the practice of ICT teacher capacity building in prosperous education countries in Asia based on PISA scores, Singapore and South Korea are still valuable. Prosperous education countries positively impact the advancement of ICT teacher capacity building. This evidence will be fruitful for the ICT teacher capacity building in Indonesia since Indonesia's PISA score is lower than Singapore's and South Korea's. This paper (1). identify the key secret of ICT teacher capacity building practices in the foremost Education among Asia countries, (2). to offer several considerations based on key secret practices which may enable Indonesia to take a lesson to transfer it in Indonesia context.